2002
DOI: 10.1111/1467-6486.00284
|View full text |Cite
|
Sign up to set email alerts
|

Public and Private Management: What’s the Difference?

Abstract: Critics of New Public Management argue that differences between public and private organizations are so great that business practices should not be transferred to the public sector. In this paper the theoretical arguments on the differences between private firms and public agencies are reviewed, and 13 hypotheses are identified on the impact of publicness on organizational environments, goals, structures and managerial values. Evidence from 34 empirical studies of differences between public agencies and privat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
869
8
55

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,084 publications
(1,016 citation statements)
references
References 0 publications
23
869
8
55
Order By: Relevance
“…This study's main contribution is adding to the public-private comparison literature by including non-American data and overcoming the problems of temporal bias, lack of diversity, and respondent bias (Boyne, 2002). This study has expanded the Brazilian literature significantly by providing results based on data from Brazilian public and private sectors and by accounting for cultural specificities.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study's main contribution is adding to the public-private comparison literature by including non-American data and overcoming the problems of temporal bias, lack of diversity, and respondent bias (Boyne, 2002). This study has expanded the Brazilian literature significantly by providing results based on data from Brazilian public and private sectors and by accounting for cultural specificities.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…This study seeks to contribute to the public-private distinction literature by overcoming some limitations of previous research as pointed out by Boyne (2002) and Rainey and Bozeman (2000). The authors argue that response bias, low response rates, selection effects, weak internal validity, and social desirability responses reduce previous findings' representativeness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The similarities and differences between the public and private sectors have frequently been debated over in the literature on public administration, politics and economics (Boyne, 2002). Works of many scholars have confirmed that both public and private organizations differ in some obvious ways (Rainey, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Works of many scholars have confirmed that both public and private organizations differ in some obvious ways (Rainey, 2009). At the same time, some scholars hold the opinion that every organization, either public or private, is similar in some important respects (Murry, 1975, Boyne, 2002. Although many different interpretations and perceptions have been attained, a clear understanding of public and private organizations is yet to be established (Fottler, 1981).…”
Section: Introductionmentioning
confidence: 99%